A STUDY ON WORK DELAY OF COMPLEX BUILDINGS IN SOUTH KALIMANTAN - Syamsul Bahri (Jurnal Teknologi Berkelanjutan, 2015)
In a construction work, there is always a possibility that the time required to complete the work exceeds the allocated time. As a result, the work may experience delay that can cause harm both morally and materially, and can impact both users and service providers. Work delay will potentially occur in complex buildings. This is due to the complexity of the specification design, construction methods, the administration and the people involved. Therefore, it is necessary to conduct a study on the factors that may cause delays in construction work, the classification of construction delays, the impact of the delay, and approaches to minimize the delay in the work.This study is a non-experimental study involving five complex buildings in South Kalimantan. The objects of the study are the SAMSAT Banjarmasin Building, Department of Public Works Building, Ambulung Education Building and BAPPEDA of South Kalimantan building. The study utilizes six aspects which are divided into 45 factors causing the delay with three classifications of delay, namely excusable delay (ED), non-excusable delay (NED), and compensable delay (CD). The analysis used in this study is the analysis of data validity and reliability, descriptive analysis, as well as index and variance analysis.The result shows that the dominant factors causing the delay are the tight scheduling of the work by the owner, incorrect/incomplete planning (drawings / specifications), and the funding of the project which is not planned well (contractor funding difficulties). On the other hand, the dominant management aspect is the A aspect (Aspects of Planning and Scheduling) with an index value of 29.11. In general, the objects of study are categorized in Compensable Delay (CD) with an average index value of 27.21 as a result, the owner could not use the building within the planned schedule of operation. Measures that can be taken to minimize the delays are improving the planning at least one year before the execution of the work, conducting periodic meetings so that the problems that occur in the field can be monitored and resolved quickly, strengthening the supervisory role of the consultant in controlling costs, time, and methods of the contractor, and establishing good communication between the owner, contractors, and consultants in the management supervisory work.